2011
DOI: 10.1080/00423110903410526
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of semi-active suspensions with control of variable damping and stiffness

Abstract: 2011) Performance analysis of semi-active suspensions with control of variable damping and stiffness, Vehicle System Dynamics: InternationalThe problem considered in this paper is the study and the control strategy design of semi-active suspensions, featuring the regulation of both damping and stiffness. The first contribution of this paper is the introduction and the analysis of two architectures based on the use of only controllable dampers, which make possible the emulation of an ideal suspension with contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…The results showed that the variable stiffness and damping suspension performed best in isolating vibrations. Following their work, Spelta et al developed a novel control algorithm to control the variable stiffness and damping suspension in order to further improve the ride comfort of vehicles [23]. The simulation result demonstrated that the variable stiffness and damping suspension controlled by their control algorithm was more efficient in improving vibration isolation performance than the suspensions with only variable damping.…”
mentioning
confidence: 96%
“…The results showed that the variable stiffness and damping suspension performed best in isolating vibrations. Following their work, Spelta et al developed a novel control algorithm to control the variable stiffness and damping suspension in order to further improve the ride comfort of vehicles [23]. The simulation result demonstrated that the variable stiffness and damping suspension controlled by their control algorithm was more efficient in improving vibration isolation performance than the suspensions with only variable damping.…”
mentioning
confidence: 96%
“…The effectiveness of variable stiffness and damping on vibration reduction has been fully verified through simulation [20][21][22], however, a practical device that stiffness and damping are controllably simultaneously has been seldom developed.…”
Section: Introductionmentioning
confidence: 99%
“…The work reported by Spelta et al [20] and Xu et al [21] are the conceptual designs of variable stiffness and damping structure. Their simulation applied the variable stiffness and damping device on a vehicle suspension and the results verified that it is better at reducing vibrations than the suspension with only variable damping.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, S t and S t−1 represent the smoothing values for the lake areas at times t and t − 1, respectively, and a is the smoothing coefficient, namely, the damping coefficient [38]. Y t−1 is the actual lake area at t − 1.…”
Section: The Quadratic Exponential Smoothing Modelmentioning
confidence: 99%